From Tokyo to Manila: The adaptation of halal Japan application system in promoting halal awareness in the Philippines - Cahyadi, Eko Ruddy; Azahra, Revina Novri; Fabian, Haikal; Latisya, Putri (IPB University, 2024)
The adaptation of the Halal Japan Application System is able to serve as a model to promote halal awareness in the Philippines. This is because the country has a Muslim minority and significant potential for the growth of the halal industry. The concept of Halal, derived from Islamic teachings, covers more than dietary restrictions by influencing lifestyle choices and consumer behavior across diverse sectors, including food, cosmetics, and tourism. Therefore, this research aimed to discuss the challenges and opportunities within the halal certification landscape in both Japan and the Philippines. The trend is associated with the persistence of issues such as the lack of a centralized regulatory body and varying standards among certifying agencies in Japan despite the advancements in halal certification since 2010 and the development of the Halal Japan app. Meanwhile, the Philippines faces infrastructural and awareness challenges in its burgeoning halal sector. The implementation of a similar halal app could bridge these gaps, enhancing accessibility and reliability for local and international Muslim communities. This comparison showed the need to improve the certification processes and community engagement strategies to establish the Philippines as a key player in the global halal market in order to foster economic growth and cultural integration.